Governança global e a visão brasileira das organizações e regimes pós-2008 - Arab, Miguel Angelo (2012)
In the first chapter, this study will analyze the follow question of research: how the 2008 global financial crisis affected the global balance of power; their impact on the international system developments; their respective argument goals; and the definition and relevance of this study. In the chapter 2, this study will determinate the methodological point of view in terms of approach and of collecting and processing information methods. The third chapter will present the complexity of the interaction between the international order and the global governance. These two terms are very difficult to define, but they are frequent on the agenda of diplomacy and in the international politics. In chapter 4, this study will introduce the multilevel governance concept to express the interaction between several actors in several layers below and above the state. The fifth chapter will examine the crisis that occurs before the 2008 global financial crisis, investigating the possible existence of common characteristics between them. In the sixth chapter, this work will investigate the 2008 global financial crisis and their extension and prolongation to Europe, enunciating the economic and financial global variables. This work, in the Chapter 7, attempts to relate Brazil's foreign policy to the of global governance architecture, targeting more active contribution in international forums. In chapter nine, this text will presents the conclusion of this study in terms of dilemmas and the behavioral and/or structural obstacles and the questions that should be considered and deeply investigated